PERSEPSI PESERTA DIDIK PADA MEDIA POWERPOINT DALAM GOOGLE CLASSROOM - Lily Parnabhakti; Nicky Dwi Puspaningtyas (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
This study aims to describe the perceptions of students on powerpoint media in google classroom to improve student learning outcomes in mathematics subject matter of the limit of algebraic functions. Samples were selected randomly using the purposive solvin method and selected class XI MIPA2 SMA N 5 Bandarlampung as the experimental class. 36 students from three classes were sampled in this study. The research instrument was in the form of a questionnaire. The type of questionnaire used was a closed questionnaire. Closed questionnaire is a questionnaire that is presented with several choice questions which will be answered by respondents. The questionnaire model used is the Linkert scale questionnaire model. The Linkert model scale in this study uses a rating range scale (Strongly Agree, Agree, Disagree, Strongly Disagree). Based on the research, it can be concluded that the relevant powerpoint media is used in learning the material for limiting algebraic functions for class XI MIPA 2 at SMA Negeri 5 Bandar Lampung, this learning media also makes it easier for students to learn using google classroom during the COVID-19 pandemic.Keywords: analysis, Powerpoint Media, COVID-19